Augmentation of biocontrol agents with physical methods against postharvest diseases of fruits and vegetables. (November 2017) - Zhang, Hongyin; Mahunu, Gustav Komla; Castoria, Raffaello; Apaliya, Maurice Tibiru; Yang, Qiya
Abstract: Background: The application of physical (thermal and non-thermal) treatments in combination with biocontrol agents for the control of postharvest fungi has achieved significant research attention. In order to make combined nonchemical agents commercially suitable for postharvest treatment of other commodities, there is the need to study their individual effects and then integrated effects to present them as economically viable, resilient and persistent. Scope and approach: In this article, various physical treatment methods (thermal and non-thermal) have been used to enhance the bioefficacy of microbial agents against postharvest diseases of fruits and the possible mode of action were reviewed. Additionally, the interrelationship between fungal virulence, host response and environmental factors that influence infection rate and production of mycotoxin has also been highlighted. Key findings and conclusions: Physical treatments act as disinfectants of surfaces of produce prior to application of antagonistic yeasts that provide persistent protective action over an extensive period. Physical methods by heat treatment tends to seal or cure openings on the produce in order to limit the sites for pathogen penetration and restriction of secondary infections by biofilm formation after application of antagonistic yeasts or bioactive compounds. Thus, this phenomenon slow down changes in fruits respiration and metabolic activity. Heat has the potential to up-regulate proteins in fruits, which correlates with defense response and redox metabolism; consequently, demonstrates a physiological adaptation to environmental stress. From literature, there is limited information on the effect of ohmic heat method combined with antagonistic on decay causing pathogens and shelf life of fruits. Furthermore, the employment of novel tools available in molecular biology will enable in-depth explanation of other physiological and biochemical pathways on which the treatment effects are supported. Highlights: Physical treatments alone can disinfect the surfaces of diseases but cannot prevent secondary infections. Physical methods combined biocontrol agents can improve the persistence and reliability of treatment effects. Combine treatments operate additively or synergistically to favour induction of host disease resistance.